ANALISIS KESESUAIAN WISATA DIVING DI KAWASAN PERAIRAN PULAU KUNYIT SEBELAH TIMUR KECAMATAN PULAU LAUT TANJUNG SELAYAR KABUPATEN KOTABARU - Abdul Koriyandi; Hamdani Hamdani; Dafiuddin Salim (Universitas Lambung Mangkurat, 2016)
The waters of Kunyit Island on the east is one of the coastal waters in Kotabaru Regency that has the potential for marine tourism. However, in development is still a lot of obstacles, including the suitability of land for marine tourism have not been identified. Utilization of coastal and marine resources in the waters of Kunyit Island on east may be the development of marine tourism such as diving. The purpose of this study was to determine the suitability of land suitability level of marine tourism in the waters of Kunyit Island on east based on physical oceanographic parameters and BioEcology. The method used is the descriptive method with the help of analysis Travel Suitability Index (IKW) which generates the conformity travel. The results of this study indicate that the results of marine tourism suitability for diving in a class quite suitable (S2) with an area of 17.44 ha (78.72%) and is not suitable (N ) with an area of 4.71 ha (21.28%).